Forming digital kinships with earthen materials. The T-Stool - Rhett Russo (Agathón)
This paper aims to address how the ceramic process has been conceptualized to develop a new kinship between ceramic and its counterparts through digital technology. The interface between ceramic materials and digital fabrication, outlined here initiates a new collaboration between the real and the digital, whose interactions are tentacular. The design framework aims to rigorously leverage the vibrancy of matter in the design process. The methodology chronicles the fabrication of the T-Stool, as part of interdisciplinary collaboration, to develop a novel press-molding technique for stoneware that uses a two-part, silicone rubber and epoxy mold. The T-Stool was executed in stoneware through the use of a digital twin as a data source for material speculation, to track transformations in the clay, and to implement the use of custom tools.